PENGEMBANGAN DIGITAL MARKETING DALAM MEMPERLUAS PEMASARAN PRODUK KERAJINAN ECOPRINT DI DUTA CRAFT MOJOROTO, KOTA KEDIRI - Ahmad Yani; Nandita Eka Saputri; Natasya Fadila Romli; Ninda Zulva; Nita Indah Sari; Nafis Solehudin (Journal of Community Service (JCOS), 2024)
In today's modern era, the world of business and marketing has undergone a fundamental transformation thanks to advances in digital technology. The assistance is held at the Duta Craft location, Jl. Veteran, Gg IV, No. C-13, Mojoroto, Kediri City. The method of implementing work assistance for the development of digital marketing is carried out through the stages of observation, planning, implementation and evaluation with the aim of expanding the marketing reach of ecoprint craft products in building an advanced and developing business venture. While the analytical method used is a naturalistic method with a qualitative approach. The results obtained from ecoprint products that are environmentally friendly and have a high selling value are known to the wider community through various available websites and Google Maps.